Lobbying in American political system - Palekar, S.A. (2006)
A very popular means used by pressure groups in American Political System is Lobbying. It involves the art of cultivating and influencing the policy makers, legislators, judges and civil servants. Pressure groups use lobbying for influencing them in favour of their interests. No doubt, the technique of lobbying has its own set of evils, but the Americans have their own notions about its legitimacy. To them it may be regulated but not outlawed as its abolition would amount to the infringement of the essential liberties relating to speech and expression as provided in the constitution by the First Ten Amendments. To them the principal method of regulating lobbying is disclosure rather than control. It is also feared by many people that severe restrictions on the tactic of lobbying would hamper legitimate method of influencing the decision-makers without checking more serious abuses. - Reproduced.
Keywords: United States - Politics and government; Interest groups - United States; Politics and government